2021
DOI: 10.20944/preprints202105.0735.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin as a Natural Remedy for Atherosclerosis: A Pharmacological Review

Abstract: Curcumin, a hydrophobic bioactive constituent from Curcuma longa, has several health promoting properties including anti-atherosclerotic properties. Further, curcumin has blood glucose- and lipid-lowering properties, prophylactic, and therapeutic effects in other cardiometabolic diseases. Atherosclerosis is an umbrella term for a series of degenerative and hyperplasic lesions such as thickening or sclerosis in large and medium -sized artery walls that decrease vascular-wall elasticity and lumen diameter. The a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 56 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Curcumin has aromatic parts, such as an O‐methoxy phenolic and β‐dicarbonyl group. There are various biological properties and therapeutic benefits of curcumin that can be utilised for the treatment of chronic human disease, as it possesses antioxidant, anti‐inflammatory, anticancer, antidiabetic, immune‐regulatory, cardiovascular protective, neuroprotective and hepatoprotective effects 141–143 …”
Section: Natural Compounds As Cancer Preventive and Therapeutic Agent...mentioning
confidence: 99%
“…Curcumin has aromatic parts, such as an O‐methoxy phenolic and β‐dicarbonyl group. There are various biological properties and therapeutic benefits of curcumin that can be utilised for the treatment of chronic human disease, as it possesses antioxidant, anti‐inflammatory, anticancer, antidiabetic, immune‐regulatory, cardiovascular protective, neuroprotective and hepatoprotective effects 141–143 …”
Section: Natural Compounds As Cancer Preventive and Therapeutic Agent...mentioning
confidence: 99%
“…Growing evidence has delineated that CUR can regulate different signaling molecules to retard the progression and development of atherosclerosis (Li et al, 2020; Momtazi‐Borojeni et al, 2021). It can down‐regulate inducible nitric oxide synthase activity that controls the nitro−/oxidative‐stress (Singh et al, 2021), and was reported to promote the increase in the peroxisome proliferator‐activated receptor gamma (PPAR‐γ) activity to inhibit the proliferation of vascular smooth muscle cells (VSMCs), and their migration to the intima and its associated complications such as intimal thickening in cases of atherosclerosis due to hyperlipidemia. In fact, neointimal responses related to artery damage cause proliferation, migration, and collagen synthesis in VSMCs, which increase the atherosclerotic tendency (Han et al, 2019; Hatamipour et al, 2021; Singh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It can down‐regulate inducible nitric oxide synthase activity that controls the nitro−/oxidative‐stress (Singh et al, 2021), and was reported to promote the increase in the peroxisome proliferator‐activated receptor gamma (PPAR‐γ) activity to inhibit the proliferation of vascular smooth muscle cells (VSMCs), and their migration to the intima and its associated complications such as intimal thickening in cases of atherosclerosis due to hyperlipidemia. In fact, neointimal responses related to artery damage cause proliferation, migration, and collagen synthesis in VSMCs, which increase the atherosclerotic tendency (Han et al, 2019; Hatamipour et al, 2021; Singh et al, 2021). However, the desirable pharmacological activities of CUR are hampered by its poor solubility, which consequently leads to low bioavailability (Ahmed‐Farid et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, extensive research has been carried out to study the application of CUR as a health improving agent and used as a functional ingredient in foods. 15 Yadav et al 16 reported that CUR protects arsenic-induced neurobehavioral toxicity by modulating oxidative stress and dopaminergic function in rats. It may be a significant concern whether CUR can be of use in treatment of neuronal damage caused by TBPH exposure.…”
Section: Introductionmentioning
confidence: 99%